Local Er(III) environment in luminescent titanosilicates prepared from microporous precursors - Rainho, J. P.; Pillinger, M.; Carlos, L. D.; Ribeiro, SJL; Almeida, R. M.; Rocha, J. (Royal Soc Chemistry, 2002)
The local environment of Er3+ ions in microporous titanosilicate ETS-10 and in synthetic narsarsukite and glassy materials obtained by calcination of ETS-10 has been investigated by EXAFS, Raman and photoluminescence spectroscopies. Er L-III-edge EXAFS studies of Er3+-doped ETS-10 support the view that the exchanged Er3+ ions reside close to the (negatively charged) TiO6 octahedra. In ETS-10, Er3+ is partially bonded to framework oxygen atoms and hydration water molecules. The Er...Ti distance (3.3 Angstrom) is similar to the Na...Ti distances (3.15-3.20 Angstrom) reported previously for Na-ETS-10. Although the exact location of the ErO6 units within the host structure of Er3+-doped synthetic narsarsukite is still an open question, it is most likely that Er3+ substitutes Ti4+ rather than Na+ ions. EXAFS spectroscopy indicates that no significant clustering of erbium atoms occurs in the titanosilicate samples studied. Evidence for the insertion of Er3+ ions in the framework of narsarsukite has been obtained by Raman spectroscopy. This is indicated by the increasing full-width at half-maximum (FWHM) of the 775 cm(-1) peak and the increasing intensity of the anatase peaks as the erbium content increases. In addition, as the narsarsukite Er3+ content increases a band at ca. 515 cm(-1) firstly broadens and subsequently a new peak appears at ca. 507 cm(-1).Er3+-doped narsarsukite exhibits a characteristic local vibrational frequency, (h) over bar omega ca. 330 cm(-1), with an electron-phonon coupling, g ca. 0.2, which constitutes additional evidence for framework Er3+ insertion. The number of lines in the infrared emission spectrum of synthetic narsarsukite indicates the presence of two optically-active erbium centres with very similar local environments and an average I-4(13/2) lifetime of 7.8 +/- 0.2 ms.